2019
DOI: 10.1177/0093854818824371
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Time Spent in Restrictive Housing Confinement on Subsequent Measures of Institutional Adjustment Among Men in Prison

Abstract: Proponents of restrictive housing argue that its use is an effective deterrent of antisocial behavior, while its critics maintain that the setting causes serious psychological damage and increases noncompliance with institutional rules and expectations. Unfortunately, few studies exist that examine the influence of restrictive housing on behavioral outcomes. This investigation adds to this gap in knowledge by assessing the impact of time spent in restrictive housing confinement on subsequent measures of instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 38 publications
7
46
0
Order By: Relevance
“…Our findings replicate other studies showing inmate segregation does not substantively affect inmates' subsequent infractions or reconvictions once in the community (e.g., Clark & Duwe, 2017;Labrecque, 2019;Lucas & Jones, 2017;Morris, 2016).…”
Section: Organizational Practice and Policiessupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings replicate other studies showing inmate segregation does not substantively affect inmates' subsequent infractions or reconvictions once in the community (e.g., Clark & Duwe, 2017;Labrecque, 2019;Lucas & Jones, 2017;Morris, 2016).…”
Section: Organizational Practice and Policiessupporting
confidence: 90%
“…Finally, we excluded inmates with a designated mental health condition as their cognitive abilities were potentially mismatched with the rationality assumptions of deterrence theory. While this may have introduced some bias into our findings (recent research shows that inmates with psychological problems comprise up to 30% of inmates in some restrictive Beck, 2015); the results of our study are consistent with those of similar research designs including mentally ill offenders (e.g., Clark & Duwe, 2017;Labrecque, 2019Labrecque, , 2015 as well as those that did not include these offenders (e.g., Lucas & Jones, 2017;Mears & Bales, 2009;Morris, 2016). Prior research indicates that the greater the methodological rigor of study designs assessing solitary confinement and subsequent inmate behavior, the weaker its effects (Morgan et al, 2016) and our results are consistent with this finding.…”
Section: Study Limitationssupporting
confidence: 85%
See 2 more Smart Citations
“…However, there is a shortage of empirical evidence demonstrating that SC truly accomplishes these aims (4). In fact, studies have shown that SC fails to reduce institutional misconduct in inmates (3,(9)(10)(11)(12)(13) and could even increase said misconduct (3,14). SC has also been associated with an increase in subsequent recidivism or rule-breaking in community (15)(16)(17) and might therefore have adverse effects which outlive incarceration.…”
Section: Introductionmentioning
confidence: 99%